2006
DOI: 10.1136/thx.2006.059469
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of organising pneumonia in Iceland

Abstract: Background: Cryptogenic organising pneumonia (COP) has also been called idiopathic bronchiolitis obliterans organising pneumonia. In secondary organising pneumonia (SOP) the causes can be identified or it occurs in a characteristic clinical context. The aim of this study was to determine the incidence and epidemiological features of COP and SOP nationwide in Iceland over an extended period. Methods: A retrospective study of organising pneumonia (OP) in Iceland over 20 years was conducted and the epidemiology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 12 publications
0
40
0
3
Order By: Relevance
“…According to a recently published nationwide epidemiology study in Iceland, the mean annual incidence of OP (both cryptogenic and secondary) was 1.97 per 100 000 people, which is much higher compared to the findings of other researchers [11]. Several months of illness may continue before the correct diagnosis [13,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a recently published nationwide epidemiology study in Iceland, the mean annual incidence of OP (both cryptogenic and secondary) was 1.97 per 100 000 people, which is much higher compared to the findings of other researchers [11]. Several months of illness may continue before the correct diagnosis [13,22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published results of the retrospective study in Iceland [11] showed that secondary OP occurred as often as cryptogenic OP. Secondary OP can be related to different types of medications, including amiodarone [35,36], acebutolol [35], nitrofurantoin [37], ticlopidine [38], and anticancer drugs [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 20-year review of national statistics for Iceland, the mean annual incidence of OP was 1.1 per 100,000. Onset of OP is generally in the fifth or sixth decade of life and men and women are affected equally (18). Histopathologic lesion characteristics of OP include excessive proliferation of granulation tissue, and consist of loose collagen-embedded fibroblasts and myofibroblasts, involving alveolar ducts and alveoli.…”
Section: Wwwrespircasecommentioning
confidence: 99%
“…No tiene diferencias por género y puede presentar fiebre, disnea, tos, crépitos inspiratorios de evolución aguda o subaguda 28,29 .…”
Section: Neumonía Criptogénica Organizadaunclassified